Fabrication of VO2-Dispersed Glass in B2O3-P2O5-V2O5 System and Its Thermal Property - Muramoto, Kei; Takahashi, Yoshihiro; Terakado, Nobuaki; Yamazaki, Yoshiki; Suzuki, Shigeru; Fujiwara, Takumi (Frontiers in Materials, 2020)
Phase change material (PCM), which enables a heat storage based on phase transition, plays an important role for efficient energy utilization. This paper briefly describes our recent study about all-solid PCM by combination of vanadium dioxide (VO2) with latent heat storage capacity and multicomponent glass, i.e., VO2-dispersed glass. B2O3-P2O5-V2O5 glass system is used as a matrix for the VO2-dispersed glass. An attempt to describe its latent-heat storage function is given. Endothermic behaviour due to structural phase-transition of the VO2 crystals was observed in the VO2-dispersed sample, and the transition enthalpy corresponding to latent heat storage capacity was estimated to be delta-H~9.5 J/g. The value of studied sample was larger than the value of dispersed glass in BaO-TeO2-V2O5 system that is previously reported. Potential for PCM was considered in the studied sample.